Design and validation of an instrument for evaluating workplace happiness - Salazar-Altamirano, Mario Alberto; Galván Vela, Esthela; Ravina-Ripoll, Rafael; Martínez Arvizu, Orlando Josué (My University, 2026)
Workplace happiness has emerged as a strategic and ethical priority due to its impact on employee well-being, engagement, and sustainable performance. However, the construct remains conceptually fragmented, with existing measures often limited to affect or job satisfaction. This study addresses these limitations by proposing and preliminarily validating a multidimensional instrument that integrates hedonic and eudaimonic dimensions of workplace happiness: emotional well-being and purpose, work–life balance, and work relationships and support. Using a multi-phase research design, including expert content validation, a pilot study (n = 100), and large-scale psychometric testing (n = 354), the study applies exploratory and confirmatory factor analyses. Results provide initial evidence of strong structural validity, internal consistency, and convergent and discriminant validity (CFI = 0.971; TLI = 0.959; RMSEA = 0.078). Workplace happiness is conceptualised as a synergy of affective fulfilment, meaningful contribution, and supportive relationships. Despite cross-sectional and non-probabilistic limitations, the instrument offers a robust foundation for future validation and human-centred organisational research
Journal of Management & Organization
Keywords: workplace well-being; work-life balance; workplace happiness; workplace relationships; psychometric scale development; Campus Tijuana